PERANCANGAN STRATEGI KREATIF REBRANDING PROGRAM SARJANA SISTEM INFORMASI DENGAN MENGGUNAKAN METODE ADDIE - Deli Deli; Hendy (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Brand identity is a unique characteristic of a brand. Brand identity can be seen in the form of symbols, visuals, and physical representations that serve to make it easier for consumers to recognize a brand. Over the time, brand identity has become much more important and noticed. Therefore there is a demand for a brand to make changes. These changes were made to defend against extreme market developments. This process is known as rebranding, which will produce a reconstructed brand identity to compete in a new market. Corporate rebranding has become a common practice to adapt to changes in the micro and macro environment. With the increasing number of successful organizations after implementing corporate rebranding, it creates interest in the academic world, especially in universities. Therefore, the author emphasizes this application study to raise the topic of "Designing a Creative Rebranding Strategy for the Information Systems Bachelor Program". In this rebranding design stage, the research uses the ADDIE development method (Analyzing, Design, Development, Implementation, Evaluation). The output of this design will be used by Batam International University Information Systems Bachelor Program on youtube and instagram. With the implementation of this design, it will provide an identity that can reflect the new characteristics of the Batam International University Information Systems Bachelor Program.